Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.